2002
DOI: 10.1016/s0006-3495(02)73909-x
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of Forces at Focal Adhesions from Elastic Substrate Data: The Effect of Localized Force and the Need for Regularization

Abstract: Forces exerted by stationary cells have been investigated on the level of single focal adhesions by combining elastic substrates, fluorescence labeling of focal adhesions, and the assumption of localized force when solving the inverse problem of linear elasticity theory. Data simulation confirms that the inverse problem is ill-posed in the presence of noise and shows that in general a regularization scheme is needed to arrive at a reliable force estimate. Spatial and force resolution are restricted by the smoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
340
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 334 publications
(348 citation statements)
references
References 40 publications
(62 reference statements)
8
340
0
Order By: Relevance
“…3d), indicating indirectly a dependence between tension forces and vinculincontaining FA area in elongated ECs, as suggested by Balaban et al 28 For 1,600 µm 2 elongated cells, TFM measurements indicated a maximum tension of ~5.7 kPa for a total FA area of ~72 µm 2 . This result reflects an anisotropic force contraction dipole with two opposing maximum forces of ~205 nN, which is consistent with the amount of forces observed in polarized fibroblasts 35 .…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…3d), indicating indirectly a dependence between tension forces and vinculincontaining FA area in elongated ECs, as suggested by Balaban et al 28 For 1,600 µm 2 elongated cells, TFM measurements indicated a maximum tension of ~5.7 kPa for a total FA area of ~72 µm 2 . This result reflects an anisotropic force contraction dipole with two opposing maximum forces of ~205 nN, which is consistent with the amount of forces observed in polarized fibroblasts 35 .…”
Section: Resultssupporting
confidence: 86%
“…The calculated displacements were summed up to determine the overall two-dimensional displacement field. The traction field was then calculated from the displacement field by adapting the algorithm previously developed 35 . This algorithm solved the inverse of the Boussinesq solution from the displacement field on the surface of an elastic halfspace to obtain the traction field when the mechanical properties of the gel are known.…”
Section: Methodsmentioning
confidence: 99%
“…The analysis of micropillar deflection directly gives rise to the mapping of exerted forces and so could be used to follow mechanical activity in real time, in contrast with computationally intensive techniques (14-17, 29, 30). Moreover, because each pillar is independent of its neighbors, the measured traction stresses under the cells are directly and unambiguously determined (18,29).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, such techniques present limitations, mostly because, as deformations propagate on continuous surfaces, the relation between bead displacements and forces is difficult to compute. Moreover, beads form a discrete network in the surface, and these methods cannot provide force measurements between these markers (18,19). An alternative strategy has been to use an array of discrete microfabricated force sensors (cantilevers), an elegant but technologically challenging method limited also by the density of sensors on the surface (10).…”
Section: Force Mapping In Epithelial Cell Migrationmentioning
confidence: 99%
“…This approach does not directly measure the forces exerted at the individual contacts, but rather extracts them by modeling the deformation-map induced by the whole-cell. This can be a non-trivial undertaking [15]. Approaches that utilize atomic force microscopy (AFM) provide excellent resolution of the dynamical forces exerted between cells and substrates [16].…”
Section: Introductionmentioning
confidence: 99%